CEO emotional intelligence and firm dividend policy: decision tree analysis. (2017) - Azouzi, Mohamed Ali; Jarboui, Anis
This paper assumes that managers, investors or both behave irrationally. More specifically, it examines the links between managerial emotional characteristics' and firm dividend policy. This stream of research argues whether to distribute dividends or not depends on CEO emotional intelligence level. We introduce an approach based on decision tree analysis technique with a series of semi-directive interviews. The originality of this research paper is guaranteed since it treats the behavioural corporate policy choice in emergent markets. To the best of our knowledge, this is the first study in the Tunisian context that explores such area of research. Our results show that CEO emotional intelligence level encouraged using this leverage to report the decision performance of the business, the application of a dividend distribution policy.